C1 Root Decompression as a Therapeutic Target in Non-Suboccipital Non-Valsalva Related Headache Associated with Chiari I Malformation - Hergunsel, Batu; Ertugrul, Bilal; Erol, Fatih Serhat; Gonen, Murat; Kaplan, Metin (Elsevier Science Inc, 2025)
BACKGROUND: Headache (HA) is the most common symptom impacting the quality of life of patients with Chiari I malformation. While HAs typically present in the occipital or suboccipital regions, and induced by Valsalva maneuver, complex migraine-like HAs referring to frontal or orbital regions also occur. Our study explores the therapeutic potential of C1 nerve root decompression in addition to increasing intracranial compliance in patients with Chiari I malformation. METHODS: We retrospectively analyzed cases operated on for Chiari I malformation, focusing on patients with nonsuboccipital, non-Valsalva induced HAs. Preoperative and postoperative visual analog scale scores and HA frequency were recorded. Surgical technique involved sub- occipital craniectomy, C1 laminectomy, cerebellar tonsil reduction, and C1 root decompression. RESULTS: Twelve patients (10 females, 2 males) aged 2252 years were included. Preoperative mean visual analog scale score was 8, which improved to 2 or less in 11 patients postoperatively. The mean HA frequency decreased significantly. CONCLUSIONS: Our findings suggest that C1 root compression contributes to atypical HAs in Chiari I malformation and that C1 root decompression may improve surgical outcomes.
Keywords: Clinical Anatomy